Rancang Bangun Aplikasi Game Pembelajaran Augmented Reality Berbasis Android Dengan Metode Co-CreaARGBL (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
In a time of pandemic like this, all sector activities, in urban and rural areas, become very difficult and activities are limited. The public is asked to maintain health protocols by using masks, washing hands, maintaining distance, and staying away from crowds. Many activities such as school, working, and worship and many other activities that can gather many people do online with the help of video conferencing support software. Institution for teaching and learning activities including those affected by the Coronavirus Disease 2019 (COVID-19) caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). The impact of activities carried out online and carried out almost every time in the world of learning is a decrease in participants’ enthusiasm due to boredom and monotonous impression without further interaction between participants and interactive media. So from these problems it is felt that there is a need for new media that can make online video conferencing learning activities not bored, which can make participants more active and not get bored easily during video conference. By using the Co-CreaARGBL method, making interactive augmented reality game-based learning media into a fun learning game with 3 main stages, that a Training, Interactive Design, and Classroom Evaluation, so that online learning becomes easy and fun by combining interactive multimedia elements that make participants interact more with fun learning media so they are not easily bored and seem monotonous.